Plane waves in thermo-viscoelastic material with voids under different theories of thermoelasticity - Tomar, S.K.; Goyal, N.; Szekeres, A. (Zielona Góra: Uniwersytet Zielonogórski)
Propagation of time harmonic plane waves in an infinite thermo-viscoelastic material with voids has been investigated within the context of different theories of thermoelasticity. The equations of motion developed by Iesan [1] have been extended to incorporate the Lord-Shulman theory (LST) and Green-Lindsay theory (GLT) of thermoelasticity.
Keywords: thermo-visco-elasticity; voids; waves; phase speed; attenuation; energy